2016
DOI: 10.1088/1475-7516/2016/04/055
|View full text |Cite
|
Sign up to set email alerts
|

On D-brane -anti D-brane effective actions and their all order bulk singularity structures

Abstract: All four point functions of brane anti brane system including their correct all order α ′ corrections have been addressed. All five point functions of one closed string Ramond-Ramond (RR), two real tachyons and either one gauge field or the scalar field in both symmetric and asymmetric pictures have also been explored. The entire analysis of < C −2 A 0 T 0 T 0 > is carried out. Not only does it fix the vertex operator of RR in asymmetric picture and in higher point functions of string theory amplitudes but als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 112 publications
0
17
0
Order By: Relevance
“…In previous works, it has been shown that Dφ i(1) • Dφ i(2) -couplings are required on the worldvolume of DD systems for consistency between EFT and worldsheet descriptions[94].…”
mentioning
confidence: 99%
“…In previous works, it has been shown that Dφ i(1) • Dφ i(2) -couplings are required on the worldvolume of DD systems for consistency between EFT and worldsheet descriptions[94].…”
mentioning
confidence: 99%
“…It is worth to pointing out that the appearance of F (1) · F (2) and also Dφ i(1) · Dφ i (2) couplings for D-brane-Anti D-brane DBI action have been confirmed by direct consistent string amplitudes of [26] and [38] accordingly. More crucially, we got to know that C p−1 ∧ F does not receive higher derivative correction of WZ couplings.…”
Section: Lower Order D-brane-anti-d-brane Effective Actionsmentioning
confidence: 69%
“…which is exactly as derived in string theory amplitude (11). In [38] we also constructed all order α ′ corrections of one RR and two tachyons of D-brane anti D-brane system as…”
Section: Lower Order D-brane-anti-d-brane Effective Actionsmentioning
confidence: 99%
“…The preceding argument shows that this coupling is still absent even after the inclusion of higher-derivative corrections. Consequently, there are no poles in a (t + v + r )-channel, with v = v + 1 4 , r = r + 1 4 , as discussed in [38]. It is interesting to examine the effective corrections to the DBI sector of the action.…”
Section: Scalar Bulk Singularity Structurementioning
confidence: 99%